Assessors' interpretations of narrative data on communication skills in a summative OSCE. Issue 10 (15th July 2019) - Wilby, Kyle John; Dolmans, Diana H J M; Austin, Zubin; Govaerts, Marjan J B
Abstract : Objectives: Increasingly, narrative assessment data are used to substantiate and enhance the robustness of assessor judgements. However, the interpretation of written assessment comments is inherently complex and relies on human (expert) judgements. The purpose of this study was to explore how expert assessors process and construe or bring meaning to narrative data when interpreting narrative assessment comments written by others in the setting of standardised performance assessment. Methods: Narrative assessment comments on student communication skills and communication scores across six objective structured clinical examination stations were obtained for 24 final‐year pharmacy students. Aggregated narrative data across all stations were sampled for nine students (three good, three average and three poor performers, based on communication scores). A total of 10 expert assessors reviewed the aggregated set of narrative comments for each student. Cognitive (information) processing was captured through think‐aloud procedures and verbal protocol analysis. Results: Expert assessors primarily made use of two strategies to interpret the narratives, namely comparing and contrasting, and forming mental images of student performance. Assessors appeared to use three different perspectives when interpreting narrative comments, including those of: (i) the student (placing him‐ or herself in the shoes of the student); (ii) the examiner (adopting the role of examiner and reinterpreting comments according to his or her own standards or beliefs), and (iii) the professional (acting as the profession's gatekeeper by considering the assessment to be a representation of real‐life practice). Conclusions: The present findings add to current understandings of assessors' interpretations of narrative performance data by identifying the strategies and different perspectives used by expert assessors to frame and bring meaning to written comments. Assessors' perspectives affect assessors' interpretations of assessment comments and are likely to be influenced by their beliefs, interpretations of the assessment setting and personal performance theories. These results call for the use of multiple assessors to account for variations in assessor perspectives in the interpretation of narrative assessment data. Abstract : Understanding the act of interpretation is crucial to take advantage of narrative contributions to assessment. This article identifies the varied perspectives assessors adopt and their influence on the meaning derived.